Effect of formulation and repeated applications on the enantioselectivity of metalaxyl dissipation and leaching in soil. Issue 11 (19th January 2015) - Celis, Rafael; Gámiz, Beatriz; Adelino, María A; Cornejo, Juan; Hermosín, María C
Abstract BACKGROUND Soil incubation and column leaching experiments were conducted to address the question of whether the type of formulation (unsupported versus clay supported) and repeated applications of the chiral fungicide (RS)‐metalaxyl affected the enantioselectivity of its dissipation and leaching in a slightly alkaline, loamy sand agricultural soil. RESULTS Regardless of the type of formulation and the number of fungicide applications, the R‐enantiomer of metalaxyl was degraded faster than the S‐enantiomer, but the individual degradation rates of R‐ and S‐metalaxyl were highly affected by the different application regimes assayed (t1/2 = 2–104 days). Repeated applications accelerated the degradation of the biologically active R‐metalaxyl enantiomer, whereas they led to slower degradation of the non‐active S‐metalaxyl enantiomer. The type of formulation had less influence on the dissipation rates of the enantiomers. For all formulations tested, soil column leachates became increasingly enriched in S‐enantiomer as the number of fungicide applications was increased, and application of metalaxyl to soil columns as clay‐based formulations reduced the leaching of both enantiomers. CONCLUSION Pesticide application conditions can greatly influence the enantioselective dissipation of chiral pesticides in soil, and hence are expected to exert a great impact on both the biological efficacy and the environmental chiral signatures of pesticides applied as mixtures of enantiomers or racemates to agricultural soils. © 2014 Society of Chemical Industry